2018
DOI: 10.1103/physreva.98.042311
|View full text |Cite|
|
Sign up to set email alerts
|

Sharing of nonlocal advantage of quantum coherence by sequential observers

Abstract: Non-local Advantage of Quantum Coherence(NAQC) or steerability of local quantum coherence is a strong non-local resource based on coherence complementarity relations. In this work, we provide an upper bound on the number of observers who can independently steer the coherence of the observer in the other wing in a scenario where half of an entangled pair of spin-1 2 particles is shared between a single observer (Bob) in one wing and several observers (Alices) on the other, who can act sequentially and independe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 47 publications
(78 reference statements)
0
24
0
Order By: Relevance
“…Recently, a surprising result was reported by Silva et al that the number of observers sharing non-locality can be increased if the sequential weak (unsharp) measurement was employed, where the non-signaling condition is dropped [27]. Their result later is confirmed by theoretical [28][29][30] as well as experimental works [31,32], and the sequential unsharp measurement strategy has been extended to study other types of quantum correlation [33][34][35]. It has shown that the maximum number of Alices who can simultaneously share steering with a single Bob can also beat the steering monogamy limits [36][37][38].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, a surprising result was reported by Silva et al that the number of observers sharing non-locality can be increased if the sequential weak (unsharp) measurement was employed, where the non-signaling condition is dropped [27]. Their result later is confirmed by theoretical [28][29][30] as well as experimental works [31,32], and the sequential unsharp measurement strategy has been extended to study other types of quantum correlation [33][34][35]. It has shown that the maximum number of Alices who can simultaneously share steering with a single Bob can also beat the steering monogamy limits [36][37][38].…”
Section: Introductionmentioning
confidence: 95%
“…In this scenario, the maximum number of Bobs was deduced [20][21][22][23][24][25] that can demonstrate Bell nonlocality [26]. This idea of sharing quantum correlations by multiple sequential observers has been extended in different contexts as well [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The applications of sequential sharing of quantum correlations in different quantum information processing tasks have also been demonstrated [16,[43][44][45][46][47][48][49][50].…”
mentioning
confidence: 93%
“…The question of sharing of quantum correlations was first raised in the context of Bell-nonlocality [25,26], and has been experimentally demonstrated too [29][30][31]. Studies on sequential sharing of quantum correlations have been extended in several different directions, such as Bell-type nonlocality with multiple settings [32,33], detection of entanglement [34,35], detecting bipartite [36,37], and tripartite steerability [38], steerability of local quantum coherence [39], potential shareability of a teleportation channel [40] and generation of unbounded randomness [41]. In all the above cases, each Bob at the clustered side implements unbiased and unsharp measurement for all chosen observables.…”
Section: Introductionmentioning
confidence: 99%